The monitoring actions on the project “Didactics for competences”of UNIMORE - Cecconi, Luciano; Bellini, Claudia (Formazione & insegnamento, 2019)
The paper presents the actions and results of the monitoring made on the perceptions of the actors involved in the three-year project “Didactics for competences”, activated at the University of Modena and Reggio Emilia (UNIMORE) for the academic years 2016-2019 with the intent of developing problem solving and team working skills in the students. The project, which required the testing of active teaching methods on a number of subjects in the economic-social, health and scientific areas, involved a large number of teachers, students and tutors. The purpose of the monitoring, based on the use of questionnaires and focus groups, was to detect the perceptions of these actors regarding the didactic experimentation, in particular of the didactic methodology adopted: Team Based Learning. The paper presents the tools, actions and results of the monitoring with the aim, in the short term, to highlight strengths and weaknesses of the project and, in the future, to define the characteristics of a good teaching practice to be taken as a reference for future dissemination at university level.